MEMPERSIAPKAN BISNIS ONLINE BAGI PRODUK SASIRANGAN DI KELURAHAN SUNGAI MESA KOTA BANJARMASIN - Basuki Basuki; Zakky Zamrudi; Hairul Hairul (Universitas Islam kalimantan MAB, 2019)
Sasirangan cloth industry continue to grow through Banjarmasin and South Kalimantan in general. Supporting of the government and the other parties, sasirangan industry be one of locomotion economic the people who could not being taken from granted. Almost hundreds of home industries have good scale, micro and small thrives in South Kalimantan income of a whole reach millions until even billions of rupiah per month. Increasing competition in cloth industry they need to in open opportunities marketing via internet. Basically between business online and the internet marketing have in common meaning or similar signification, same has objective to earn a living through digital world. But for the internet marketing more oriented to techniques get money from the online business.